ADAPTASI ALAT UKUR STUDENT SUBJECTIVE WELL-BEING QUESTIONNAIRE (SSWQ) VERSI BAHASA INDONESIA - Handayani, Winna Andini; Purnama, Chandra Y.; Sari, Rina (Universitas Gunadarma, 2024)
This study adapts and analyzes the psychometric properties of the Student Subjective Well-being Questionnaire developed by Renshaw in Indonesian with a sample of students. The adaptation of this measuring instrument goes through several stages, starting from translation, back translation, testing the reliability coefficient and collecting validity evidence in the form of content-based testing and internal structure testing using confirmatory factor analysis (CFA). This study involved a sample of 296 high school students in Cimahi City. Testing the reliability of the Indonesian version of SSWQ, the Cronbach alpha result was 0.84. In addition, testing the evidence of internal structure using CFA shows that the Indonesian version of the SSWQ instrument has an acceptable goodness of fit index (RMSEA=0.03, SRMR=0.03, CFI=0.98, and p-value chi squre=0.086). The factor loadings of the items were in the range of 0.54-0.768. It can be concluded that the Indonesian version of the SSWQ measuring instrument has good psychometric properties so that it can be used for research or assessment purposes to measure student well-being in schools that are brief, valid and reliable. This study suggests that the Indonesian version of the SSWQ is developed with a wider variety of samples with a larger sample size.